2013
DOI: 10.1007/s00391-012-0463-7
|View full text |Cite
|
Sign up to set email alerts
|

Betreuungsindex in Pflegeheimen

Abstract: The NCI has a double function. Nursing staff and management can now use the NCI to conduct internal quality assurance regarding their caring efforts. In the future, the NCI can become a useful tool for families and residents to compare the quality of care in different nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…caring, dementia, family, needs, nursing, nursing home, palliative care, quality of life well-being in various domains. Therefore, the quality of life for PWD seems to be sensitive to psychological and behavioural symptoms, cognitive and functional decline and the caring quality a PWD experiences (Banerjee et al, 2009;Koppitz et al, 2013). Ellis-Smith (2018) reported that the use of the IPOS-Dem improved aspects of caring quality for PWD.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…caring, dementia, family, needs, nursing, nursing home, palliative care, quality of life well-being in various domains. Therefore, the quality of life for PWD seems to be sensitive to psychological and behavioural symptoms, cognitive and functional decline and the caring quality a PWD experiences (Banerjee et al, 2009;Koppitz et al, 2013). Ellis-Smith (2018) reported that the use of the IPOS-Dem improved aspects of caring quality for PWD.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, RN in Swiss nursing homes are involved with quality and innovation (Zúñiga et al, 2021 ). Frontline staff in nursing homes establish caring relationships based on systematic observation of needs (Koppitz et al, 2013 ). For this study, and like that articulated by Watson ( 2008 ), caring is defined as a moral imperative and ethical foundation of nursing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations